Workforce Diversity: A Spotlight on Employee Sustainability Excellence in India - AISWARYA Balachandar; RAMASUNDARAM Gurusamy; SUDHA Paulin; POONDY Rajan (Foundations of Management)
This research paper explores a crucial yet often underestimated nexus: the relationship between workforce diversity and employee sustainability in the vibrant television media industry. Through an indepth examination of diverse dimensions such as age, gender, culture, and socio-behavioral factors, it illuminates how these elements intricately influence the long-term viability of employees within this rapidly evolving sector. The paper's standout feature lies in its rigorous statistical analyses, which uncover the nuanced connections between workforce diversity and employee sustainability. By grounding its findings in empirical evidence, the paper transcends mere conjecture, offering a robust framework for comprehending and tackling this pressing issue. Moreover, the spotlight on the Indian media industry brings a unique perspective, given its extraordinary growth trajectory and substantial economic impact. Readers stand to gain invaluable insights into the dynamics of diversity within this context, potentially yielding transferable lessons and strategies for other industries and regions. In its culmination, the paper presents a synthesis of actionable recommendations and conclusive insights, serving as a practical guide for organizations seeking to harness diversity as a catalyst for long-term employee sustainability. With its blend of academic rigor and real-world relevance, this paper is indispensable reading for industry practitioners, policymakers, and scholars alike.